Coastal mapping using Unmanned Aerial Vehicle (UAV) system: case study Cyrstal Bay, Alai Melaka / Norhadija Darwin ... [et al.] - Darwin, Norhadija; Ahmad, Anuar; Zainon, Othman; Mat Amin, Zulkarnaini (Universiti Teknologi MARA, Pulau Pinang, 2015)
Coastal erosion is regarded as one of the most pressing areas due to the development along the coastal line that led to the host of problems such as sea level rise along the coast, siltation and loss of coastal resource. The occurrence of coastal erosion is increasing, threatens the people living close to coastal area and caused losses along the coastal line. In addition, coastal areas are also prone to environmental hazards such as erosion and sedimentation processes may cause loss of coastal land and damage infrastructures and buildings There are many methods have been developed to map and monitor the coastal area such as total station, remote sensing technology, Global Positioning System (GPS), aerial photogrammetry and Lidar technology. The utilization of Unmanned Aerial Vehicle(UAV) system also gives an opportunity for data interoperability, data integration and data sharing that are applicable for the responsible agencies to monitor the coastal erosion and land such as state government, local authorities and land developer. UAV has been developed which offer many advantages in several mapping applications such as slope mapping, cultural heritage studies, urban deveploment, coastal and flood studies. In this study, a total of five hundred (500) aerial images of Crystal Bay, Alai Malacca were captured using high resolution compact digital camera known as Canon Power Shot SX230 HS and it has 12.1 megapixel image resolution. From the aerial images, photogrammetric image processing method was employed to produce mapping outputs such a digital surface model (DSM),contour line and orthophoto. In term of accuracy of measurement, a centimeter-level is reached by ground control point (GCP) and check point (CP) using GPS observation. Finally, the UAV has shows great potential to be used for coastal mapping applications that require goodmapping output.